IMPLEMENTASI BIMBINGAN KLASIKAL TEKNIK BRAINSTORMING SEBAGAI UPAYA PENGUATAN KESEHATAN MENTAL WARGA BINAAN LAPAS KELAS III RANGKASBITUNG - Salsabila Selma; Arga Satrio Prabowo; Raudah Zaimah Dalimunthe; Angga Sugara Febriantiko (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: This study aims to describe the implementation of classical guidance services based on the results of the AUM Umum Masyarakat assessment for inmates at Lembaga Pemasyarakatan Kelas III Rangkasbitung. The study focuses on problems related to social relationships, personal issues, and family relationship conditions among early adulthood inmates. PAR (Participatory Action Research): This study employed a Participatory Action Research (PAR) approach involving active participation between researchers and inmates during the guidance process. The subjects consisted of 50 inmates aged 18–25 years who completed the AUM Umum Masyarakat assessment. Based on the assessment results, 30 respondents with the highest problem scores in the areas of Social Relationships (HSO), Personal Self (DPI), and Family Conditions and Relationships (KHK) were selected. The implementation of classical guidance services was conducted through discussions, question-and-answer techniques, quizzes, and presentation media. Results: The findings indicated that most inmates experienced difficulties in emotional regulation, self-control when facing criticism and social judgment, and effective interpersonal communication. The implementation of classical guidance services helped participants improve emotional understanding, interpersonal communication skills, and social interaction abilities within the correctional environment.